Kajian Tokoh: Syaikh H. M. Bahri Nur Nasution dalam Perannya Berkontribusi Menyerukan Pentingnya pendalaman Pendidikan Islam Di Sekitar Tembung Medan - Nasution, Abdul Gani; Syahfitri, Andini; Mustika, Nikmah; Sipayung, Nurul Fatwa; Minta, Rahmanita; Rahmayani, Wilda (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Efforts to improve education certainly cannot be separated from the people who play a role in it. Humans as a space for study in education certainly cannot be separated from being the successors and guardians of inherited knowledge, as is the case with the actual duties of caliphs. Therefore, Shaykh H. M. Bahrin Nur Nst, voluntarily contributed to voicing Islamic education around Tembung through various actions. This thinking is of course in connection with the formation of an association of scholars or the community and the people of the khalipah-tembung port called haul. Along with this, the deepening of Islamic education is always maintained and maintained, as well as the purpose of writing this article as a form of maintenance and appreciation for the involvement of scholars in the world of Islamic education around Tembung-Medan and as a form of learning in the study of figures covering the influential history of Islamic education. Thus this article was prepared based on direct investigations or interviews, which are commonly referred to as qualitative methods which are carried out individually or in groups or in the form of conferences. Keywords: character study, history of Islamic education, contribution